Editing of StSR4 by Cas9-RNPs confers resistance to Phytophthora infestans in potato - Moon, Ki-Beom; Park, Su-Jin; Park, Ji-Sun; Lee, Hyo-Jun; Shin, Seung Young; Lee, Soo Min; Choi, Gyung Ja; Kim, Sang-Gyu; Cho, Hye Sun; Jeon, Jae-Heung; Kim, Yong-Sam; Park, Youn-Il; et al. (Frontiers in Plant Science, 2022)
Potato (Solanum tuberosum L.) cultivation is threatened by various environmental stresses, especially disease. Genome editing technologies are effective tools for generating pathogen-resistant potatoes. Here, we established an efficient RNP-mediated CRISPR/Cas9 genome editing protocol in potato to develop Phytophthora infestans resistant mutants by targeting the susceptibility gene, Signal Responsive 4 (SR4), in protoplasts. Mutations in StSR4 were efficiently introduced into the regenerated potato plants, with a maximum efficiency of 34%. High co-expression of StEDS1 and StPAD4 in stsr4 mutants induced the accumulation of salicylic acid (SA), and enhanced the expression of the pathogen resistance marker StPR1. In addition, increased SA content in the stsr4 mutant enhanced its resistance to P. infestans more than that in wild type. However, the growth of stsr4_3-19 and stsr4_3-698 mutants with significantly high SA was strongly inhibited, and a dwarf phenotype was induced. Therefore, it is important to adequate SA accumulation in order to overcome StSR4 editing-triggered growth inhibition and take full advantages of the improved pathogen resistance of stsr4 mutants. This RNP-mediated CRISPR/Cas9-based potato genome editing protocol will accelerate the development of pathogen-resistant Solanaceae crops via molecular breeding.